Industrial solid waste-based flexible composite material as well as preparation method and application thereof
By dry mixing ultrafine sand tailings, solid waste-based gelling materials, water-induced fibers and internal curing agents, and blending them with natural rubber, polybutyl acrylate and other materials, an industrial solid waste-based flexible composite material with an organic-inorganic bicontinuous phase structure is formed, which solves the problem of insufficient material performance in the existing technology, realizes the preparation of high-performance industrial solid waste-based materials, and expands the application field.
Patent Information
- Application Number
- CN202510129352.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-02-05
AI Technical Summary
In the prior art, the performance of materials prepared by industrial solid waste is not excellent enough, the performance of toughness, crack resistance and other properties are insufficient, and the application field is single.
By dry mixing ultrafine sand tailings, solid waste-based gelling materials, water-guided fibers and internal curing agents, combined with blending materials such as natural rubber and butyl polyacrylate, an industrial solid waste-based flexible composite material with an organic-inorganic bicontinuous phase structure is formed.
It improves the compressive strength, tensile strength and elongation of breaking industrial solid waste materials, enhances the toughness and crack resistance of materials, expands the application field, and reduces environmental pollution and resource waste.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to an industrial solid waste-based flexible composite material and a preparation method and application thereof. Background Art
[0002] Industrial solid waste refers to solid waste generated in industrial production activities, such as tailings generated in the process of mineral processing in mines, slag generated in the smelting of steel or other metals, fly ash generated by the combustion of pulverized coal in power plants, etc. Due to the large amount of industrial solid waste generated and the low utilization rate, a large amount of industrial solid waste is accumulated on the ground, occupying a large amount of land resources, posing environmental pollution and safety hazards. Therefore, it is urgent to reduce the amount of industrial solid waste at the source, recycle it as a resource, and treat it harmlessly.
[0003] In the Chinese invention with the publication number of CN116639945A, a method for preparing cementitious filling materials by using multi-source industrial waste slag and ultra-fine tailings is disclosed, wherein the cementitious filling materials are composed of ultra-fine tailings, industrial solid waste-based cementitious materials and water; wherein the industrial solid waste-based cementitious materials account for 6.5% to 12.5% of the total mass of the filling materials, the water accounts for 37% to 40% of the total mass of the filling materials, and the balance is ultra-fine tailings, wherein the industrial solid waste-based cementitious materials are made of steel slag, fly ash, carbide slag, desulfurized gypsum, and blast furnace slag. In the Chinese invention with the publication number of CN109206116A, a method for preparing unburned bricks using industrial tailings and fly ash is disclosed, wherein the raw materials of the unburned bricks are composed of: 25-75% industrial tailings; 5-25% at least one of cement, fly ash, and slag; 0-60% aggregate; 0-30% inorganic adhesive; and 0-10% other admixtures.
[0004] The above two patents are similar to most existing methods of treating industrial solid waste, that is, to prepare building materials by recycling industrial solid waste. Although the resource utilization of industrial solid waste is achieved, the building materials prepared by them mainly rely on inorganic materials. As a result, although the building materials can achieve a higher compressive strength, the toughness, crack resistance and other properties of the building materials are slightly insufficient, and the application field is also slightly single. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an industrial solid waste-based flexible composite material and a preparation method and application thereof, which solves the problem that the performance of materials prepared using industrial solid waste in the prior art is not good enough and the potential is insufficient.
[0006] A method for preparing an industrial solid waste-based flexible composite material comprises the following steps: S1. Dry-mixing ultrafine sand tailings, solid waste-based cementitious materials, water-diverting fibers and internal curing agents to obtain a solid waste-based dry mix; S2. The natural rubber, polybutyl acrylate, zinc oxide, stearic acid, anti-aging agent, antioxidant, vulcanization accelerator and sulfur are mixed to obtain a rubber softening material; S3. The solid waste-based dry blend obtained in S1 is mixed with the rubber softening material obtained in S2 to obtain a solid waste-based flexible composite material.
[0007] Preferably, in step S1, the particle size of the ultrafine sand tailings is 0.063-0.125 mm.
[0008] Preferably, in step S1, the amount of solid waste-based cementitious material added is 45% to 55% of the mass fraction of the ultrafine sand tailings, the amount of water-diverting fiber added is 8% to 12% of the mass fraction of the ultrafine sand tailings, and the amount of internal curing agent added is 2% to 4% of the mass fraction of the ultrafine sand tailings.
[0009] Preferably, the solid waste-based cementitious material in step S1 comprises slag powder, fly ash and water glass in a mass ratio of 1:1:0.3, wherein the fly ash is first-grade fly ash and the modulus of the water glass is 1.5.
[0010] Preferably, in step S1, the water-introducing fibers are cotton fibers with a length of 8 to 10 mm, and the internal curing agent is a highly absorbent resin with a particle size of 0.1 mm.
[0011] Preferably, step S2 is specifically as follows: mixing natural rubber and polybutyl acrylate at 110° C. for 6 minutes, then adding zinc oxide, stearic acid, anti-aging agent, antioxidant, and vulcanization accelerator and continuing to mix for 6 minutes, then cooling to 60° C. and adding sulfur and continuing to mix for 3 minutes to obtain a rubber softening material.
[0012] Preferably, in step S2, the mass ratio of natural rubber, polybutyl acrylate, zinc oxide, stearic acid, anti-aging agent, antioxidant, vulcanization accelerator and sulfur is 100: (20~40): (4.8~5.2): (1.8~2.2): (0.8~1.2): (0.8~1.2): (0.8~1.2): (1.8~2.2).
[0013] Preferably, in step S3, the solid waste-based dry mix is 30-50 parts, and the rubber softening material is 50-70 parts by weight.
[0014] The invention also provides an industrial solid waste-based flexible composite material, which is prepared by the preparation method.
[0015] The present invention also provides an application of an industrial solid waste-based flexible composite material in a composite board.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, ultrafine sand tailings are mixed with solid waste-based cementitious materials to form industrial solid waste-based solidifying materials, and highly absorbent resins and cotton fibers are added as water diversion channels and internal curing agents, and then dry-mixed without adding water, and blended with organic rubber with high elasticity and high tensile strength to form an organic-inorganic dual-continuous phase structure, and at the same time, polybutyl acrylate with high viscosity is used to modify the viscosity of natural rubber to improve the interfacial bonding strength between natural rubber and the solid waste-based dry mixture. Moreover, during the application of the industrial solid waste-based flexible composite material, the water diversion channel formed by the cotton fibers can absorb external moisture into the interior of the industrial solid waste-based flexible composite material, and the highly absorbent resin inside will store the water after receiving the moisture to form a small internal curing pool, which provides sufficient moisture for the hydration process of the industrial solid waste-based solidifying material, and no cracks are generated on the outside due to the prestressed fixation of the rubber.
[0017] 2. The industrial solid waste-based flexible composite material prepared by the present invention combines the compressive strength of mortar with the high tensile strength and high elongation at break of rubber, while improving the resource utilization of industrial solid waste, effectively reducing the environmental pollution and resource waste caused by the accumulation of industrial solid waste, and has broad application prospects. DETAILED DESCRIPTION
[0018] In order to make the technical means, creative features, objectives and functions of the present invention clearer and easier to understand, the present invention is further described below in conjunction with specific embodiments: Example 1 S1. Take 100 parts of ultrafine sand tailings, 20 parts of slag powder, 20 parts of grade 1 fly ash, 6 parts of water glass, 10 parts of super absorbent resin and 3 parts of cotton fiber, put them in a blender and dry mix them for 30 minutes to obtain a solid waste-based dry mix; S2. 100 parts of natural rubber and 30 parts of polybutyl acrylate were first mixed in a double-roll internal mixer at 110°C for 6 minutes, and then 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of an anti-aging agent, 1 part of an antioxidant and 1 part of a vulcanization accelerator were added, and the mixing was continued for 6 minutes. After the double-roll temperature was reduced to 60°C, 2 parts of sulfur were added and the mixing was continued for 3 minutes to obtain a rubber softening material; S3. Take 60 parts of the solid waste-based dry blend prepared in S1 and 40 parts of the rubber softening material prepared in S2 and mix them for 6 minutes to obtain a solid waste-based flexible composite material.
[0019] Example 2 S1. Take 100 parts of ultrafine sand tailings, 22 parts of slag powder, 22 parts of grade 1 fly ash, 6.6 parts of water glass, 8 parts of super absorbent resin and 2 parts of cotton fiber, put them in a blender and dry mix them for 30 minutes to obtain a solid waste-based dry mix; S2. 100 parts of natural rubber and 30 parts of polybutyl acrylate were first mixed in a double-roll internal mixer at 110°C for 6 minutes, and then 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of an anti-aging agent, 1 part of an antioxidant and 1 part of a vulcanization accelerator were added, and the mixing was continued for 6 minutes. After the double-roll temperature was reduced to 60°C, 2 parts of sulfur were added and the mixing was continued for 3 minutes to obtain a rubber softening material; S3. Take 50 parts of the solid waste-based dry blend prepared in S1 and 50 parts of the rubber softening material prepared in S2 and mix them for 6 minutes to obtain a solid waste-based flexible composite material.
[0020] Example 3 S1. Take 100 parts of ultrafine sand tailings, 24 parts of slag powder, 24 parts of grade 1 fly ash, 7.2 parts of water glass, 12 parts of super absorbent resin and 4 parts of cotton fiber, put them in a blender and dry mix them for 30 minutes to obtain a solid waste-based dry mix; S2. 100 parts of natural rubber and 30 parts of polybutyl acrylate were first mixed in a double-roll internal mixer at 110°C for 6 minutes, and then 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of an anti-aging agent, 1 part of an antioxidant and 1 part of a vulcanization accelerator were added, and the mixing was continued for 6 minutes. After the double-roll temperature was reduced to 60°C, 2 parts of sulfur were added and the mixing was continued for 3 minutes to obtain a rubber softening material; S3. Take 70 parts of the solid waste-based dry blend prepared in S1 and 30 parts of the rubber softening material prepared in S2 and mix them for 6 minutes to obtain a solid waste-based flexible composite material.
[0021] Example 4 S1. Take 100 parts of ultrafine sand tailings, 20 parts of slag powder, 20 parts of grade 1 fly ash, 6 parts of water glass, 10 parts of super absorbent resin and 3 parts of cotton fiber, put them in a blender and dry mix them for 30 minutes to obtain a solid waste-based dry mix; S2. 100 parts of natural rubber and 20 parts of polybutyl acrylate were first mixed in a double-roll internal mixer at 110°C for 6 minutes, and then 4.8 parts of zinc oxide, 1.8 parts of stearic acid, 0.8 parts of anti-aging agent, 0.8 parts of antioxidant and 0.8 parts of vulcanization accelerator were added, and the mixing was continued for 6 minutes. After the double-roll temperature was reduced to 60°C, 1.8 parts of sulfur were added and the mixing was continued for 3 minutes to obtain a rubber softening material; S3. Take 60 parts of the solid waste-based dry blend prepared in S1 and 40 parts of the rubber softening material prepared in S2 and mix them for 6 minutes to obtain a solid waste-based flexible composite material.
[0022] Example 5 S1. Take 100 parts of ultrafine sand tailings, 20 parts of slag powder, 20 parts of grade 1 fly ash, 6 parts of water glass, 10 parts of super absorbent resin and 3 parts of cotton fiber, put them in a blender and dry mix them for 30 minutes to obtain a solid waste-based dry mix; S2. 100 parts of natural rubber and 40 parts of polybutyl acrylate were first mixed in a double-roll internal mixer at 110°C for 6 minutes, and then 5.2 parts of zinc oxide, 2.2 parts of stearic acid, 1.2 parts of anti-aging agent, 1.2 parts of antioxidant and 1.2 parts of vulcanization accelerator were added, and the mixing was continued for 6 minutes. After the double-roll temperature was reduced to 60°C, 2.2 parts of sulfur were added and the mixing was continued for 3 minutes to obtain a rubber softening material; S3. Take 60 parts of the solid waste-based dry blend prepared in S1 and 40 parts of the rubber softening material prepared in S2 and mix them for 6 minutes to obtain a solid waste-based flexible composite material.
[0023] Comparative Example 1 Compared with Example 1, steps S2 and S3 are not performed, and only step S1 is performed.
[0024] Comparative Example 2 Compared with Example 1, no super absorbent resin and cotton fiber are added in step S1, and the remaining steps are the same.
[0025] Comparative Example 3 Compared with Example 1, polybutyl acrylate was not added in step S2, and the remaining steps were the same.
[0026] The solid waste-based flexible composite materials prepared in Examples 1-5 and Comparative Examples 2-3 were placed in a mold of 150 mm × 150 mm × 4 mm, and maintained at a constant temperature and pressure of 150°C and 15 MPa for 20 min. After cooling, they were immersed in water for 24 h, and then taken out and placed in a standard curing room (constant temperature of 20°C, humidity of 95%) for curing for 28 days. After drying, a composite board was obtained.
[0027] The solid waste-based dry mix prepared in Comparative Example 1 was added with 25 parts of water and mixed, and then placed in a 150mm×150mm×4mm mold, and then placed in a standard curing room (constant temperature 20°C, humidity 95%) for curing for 28 days, and a composite board was obtained after drying.
[0028] The compressive strength of the above-mentioned composite panels was tested according to the "Test Method for Compression Properties of Plastics" (GB / T 1041-1992).
[0029] According to "Determination of Tensile Properties of Plastics" (GB / T 1040.1-2018), the tensile strength and elongation at break of the above-mentioned composite panels were tested, and the results are shown in the following table.
[0030]
[0031] It can be seen from the above table that the composite panels prepared in Examples 1-5 have good compressive strength, tensile strength and elongation at break, and it can be seen from the performance data of the composite panels prepared in Examples 1-3 that the more the solid waste-based dry blend is added, the better the compressive strength, but the tensile strength and elongation at break will decrease accordingly, and vice versa, the compressive strength decreases, and the tensile strength and elongation at break increase. Therefore, the selection of the amount of solid waste-based dry blend and rubber softening material added is the key to balancing the compressive strength, tensile strength and elongation at break.
[0032] From the performance data of the composite boards prepared in Example 1, Examples 4-5 and Comparative Example 3, it can be seen that a small amount of polybutyl acrylate added or no addition will lead to a deterioration of the interfacial force between the natural rubber and the solid waste-based dry mix, which will comprehensively affect the compressive strength, tensile strength and elongation at break.
[0033] It can be seen from the performance data of the composite boards prepared in Example 1 and Comparative Example 1 that since no rubber softening material is added in Comparative Example 1, what is finally prepared is a traditional solid waste-based composite board. Although it has good compressive strength, its tensile strength and elongation at break are far from those of the composite board prepared in Example 1.
[0034] It can be seen from the performance data of the composite boards prepared in Example 1 and Comparative Example 2 that the compressive strength of the composite board prepared in Comparative Example 2 is obviously insufficient. The main reason is that when the solid waste-based flexible composite material is compacted and then immersed in water, there is no water diversion channel provided by cotton fibers inside, which results in that water cannot enter the interior of the solid waste-based flexible composite material and cannot be stored by the highly absorbent resin. As a result, the interior of the solid waste-based flexible composite material cannot be hydrated and solidified, and only the surface part can be solidified. Therefore, the compressive strength is obviously lower than that of the composite board prepared in Example 1.
[0035] Moreover, the solid waste-based flexible composite material prepared by the present invention is not only used for preparing composite boards, but also can be used for preparing materials in other different fields.
[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an industrial solid waste-based flexible composite material, characterized in that: The following steps are involved: S1. Dry-mixing ultrafine sand tailings, solid waste-based cementitious materials, water-diverting fibers and internal curing agents to obtain a solid waste-based dry mix; S2. The natural rubber, polybutyl acrylate, zinc oxide, stearic acid, anti-aging agent, antioxidant, vulcanization accelerator and sulfur are mixed to obtain a rubber softening material; S3. The solid waste-based dry blend obtained in S1 is mixed with the rubber softening material obtained in S2 to obtain a solid waste-based flexible composite material.
2. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S1, the particle size of the ultrafine sand tailings is 0.063-0.125 mm.
3. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S1, the amount of solid waste-based cementitious material added is 45% to 55% of the mass fraction of the ultrafine sand tailings, the amount of water-diverting fiber added is 8% to 12% of the mass fraction of the ultrafine sand tailings, and the amount of internal curing agent added is 2% to 4% of the mass fraction of the ultrafine sand tailings.
4. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S1, the solid waste-based cementitious material includes slag powder, fly ash and water glass in a mass ratio of 1:1:0.3, wherein the fly ash is first-grade fly ash and the modulus of the water glass is 1.
5.
5. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S1, the water-introducing fibers are cotton fibers with a length of 8 to 10 mm, and the internal curing agent is a highly absorbent resin with a particle size of 0.1 mm.
6. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: Step S2 is specifically as follows: mixing natural rubber and polybutyl acrylate at 110° C. for 6 minutes, then adding zinc oxide, stearic acid, anti-aging agent, antioxidant, and vulcanization accelerator and continuing to mix for 6 minutes, then cooling to 60° C. and adding sulfur and continuing to mix for 3 minutes to obtain a rubber softening material.
7. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S2, the mass ratio of natural rubber, polybutyl acrylate, zinc oxide, stearic acid, anti-aging agent, antioxidant, vulcanization accelerator and sulfur is 100: (20~40): (4.8~5.2): (1.8~2.2): (0.8~1.2): (0.8~1.2): (0.8~1.2): (1.8~2.2).
8. The method for preparing an industrial solid waste-based flexible composite material according to claim 1, characterized in that: In step S3, the solid waste-based dry mix is 50-70 parts by weight, and the rubber softening material is 30-50 parts by weight.
9. An industrial solid waste-based flexible composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the industrial solid waste-based flexible composite material according to claim 9 in composite panels.
Citation Information
Patent Citations
Production method of baking-free brick by utilizing industrial tailings and coal ash
CN109206116A
Method for preparing cemented filling material through cooperation of multi-source industrial waste residues and superfine tailings
CN116639945A
High-strength concrete based on rubber fiber compounding and preparation method thereof
CN108516775A
Fiber reinforced concrete and preparation method thereof
CN110282935A
High-crack-resistance foam concrete and preparation method thereof
CN111747691A